PENILAIAN SAFETY CULTURE PADA PEKERJA WANITA DI INDUSTRI MANUFAKTUR BERBASIS ASSEMBLY DI KOTA BATAM - Hati, Shinta Wahyu; Nur Rahmah Andayani; Adhitomo Wirawan; Bambang Hendrawan; Fedia Restu (ABEC Indonesia, 2023)
Every company has a responsibility to build a safety culture and safety climate in its work environment. As workers in the production operator section, women workers interact with the production environment, physically in contact with production tools or machines. The work of women in production as operators can be vulnerable to the risk of accidents and long-term health disruption which can ultimately have implications for the quality of life of the working women themselves and their families. The company needs to make an organised effort to realise the behaviour of awareness on safety and health of working women which is expected to have implications for the performance of women in the workplace, so it is necessary to assess (evaluate) the extent of safety culture in Assembly-based manufacturing companies in Batam. The results showed that 1). Management Commitment to Worker Behaviour is positive and significant. So Management Commitment also has a direct effect on the performance of female employees. 2) Involvement (worker involvement) has a significant effect on worker behaviour and has a direct effect on the performance of female employees.3), that Safety Competence has an effect on worker behaviour and performance of female employees. Simultaneous test results show that Management Commitment, Involvement, Safety competence and Worker behaviour have a positive and significant effect on the performance of female employees in assembly-based manufacturing companies in Batam. It can be said that assembly-based manufacturing companies have implemented safety culture for female workers in the production operator section.